2019
DOI: 10.3390/jcm8081252
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Restriction Increases the Neural Activation of the Knee Extensors During Very Low-Intensity Leg Extension Exercise in Cardiovascular Patients: A Pilot Study

Abstract: Blood flow restriction (BFR) has the potential to augment muscle activation, which underlies strengthening and hypertrophic effects of exercise on skeletal muscle. We quantified the effects of BFR on muscle activation in the rectus femoris (RF), the vastus lateralis (VL), and the vastus medialis (VM) in concentric and eccentric contraction phases of low-intensity (10% and 20% of one repetition maximum) leg extension in seven cardiovascular patients who performed leg extension in four conditions: at 10% and 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 23 publications
1
29
1
Order By: Relevance
“…However, during the KAATSU RT, the moderate blood flow restriction creates a hypoxic stimulus which is known to activate both small and large motor units, comprising, respectively, slow and fast muscle fibers [ 12 , 17 , 18 , 19 ]. Recently, we also observed that low-intensity KAATSU RT increased muscle activation during knee extension exercise in cardiovascular patients including those who have had open cardiac surgery [ 20 ]. In agreement with these previous data, here we observed that low-intensity KAATSU RT increased muscle strength and size in patients early after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the KAATSU RT, the moderate blood flow restriction creates a hypoxic stimulus which is known to activate both small and large motor units, comprising, respectively, slow and fast muscle fibers [ 12 , 17 , 18 , 19 ]. Recently, we also observed that low-intensity KAATSU RT increased muscle activation during knee extension exercise in cardiovascular patients including those who have had open cardiac surgery [ 20 ]. In agreement with these previous data, here we observed that low-intensity KAATSU RT increased muscle strength and size in patients early after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which KAATSU training potentiates the effects of low-intensity RT remain unclear, but appear to be related, in part, to an increase in muscle activation [ 12 , 17 , 18 , 19 ]. Indeed, KAATSU RT can enhance muscle activation during low-intensity knee extension exercise in cardiovascular patients with or without cardiovascular surgery [ 20 ]. Previous studies reported that KAATSU RT was accompanied by potential adverse side effects such as dizziness, subcutaneous hemorrhage, petechial hemorrhage, drowsiness, numbness, nausea, itchiness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Only five research attempts have examined the effect of low resistance BFRT in cardiovascular patients with positive results in terms of muscle strength, mass, and hypertrophy as well as the functionality of these patients [52,[58][59][60][61]. However, three of these studies are characterized by serious methodological problems as they are pilot studies and do not draw definitive conclusions [58][59][60]. In particular, they reported positive results in improving muscle strength and functionality without increasing the risk of adverse effects through hemostatic and inflammatory responses.…”
Section: Bfrt In Patients With Cardiovascular Comorbiditiesmentioning
confidence: 99%
“…Although moderate to high intensity exercise can improve muscle strength and mass in elderly 3) , they are often in cases to retire a such high intensity exercise, especially in patients with heart disease. Therefore, the low-load exercise which can Optimal KAATSU pressure increases muscle activities during low-load exercise in an elderly female frail patient receiving transcatheter aortic valve implantation Ishizaka H 1) , Uematsu A 3) , Takahashi R 1) , Ogawa H 6) , Shibasaki I 6) , Sawaguchi T 2) , Nasuno T 2) , Toyoda S 2) , Yamaguchi S 2) , Yasuda T 4) , Sato Y 5) , Fukuda H 6) , Inoue T 2) , Nakajima T 2)…”
Section: Introductionmentioning
confidence: 99%
“…Patterson et al 5) reported that, although the effect of KAATSU training to increase muscle strength and mass is weaker than high-load conventional exercise, a person who cannot perform high-load exercise such as postoperative rehabilitation, cardiac rehabilitation, inflammatory diseases, or frail elderly patients should execute KAATSU training to facilitate training effect on muscle strength and mass. Recently, because muscle activities during KAATSU training in patients with heart disease increased clearly with the load of 10% of 1 repetition maximum (RM) compared with 20% of 1 RM, we suggested that very low-load KAATSU training will be an optimal training intensity for a person with heart disease 6) .…”
Section: Introductionmentioning
confidence: 99%